KAJIAN PENGGUNAAN SERASAH DAUN KAKAO UNTUK SUBTITUSI SERBUK GERGAJI DAN DEDAK PADI SEBAGAI MEDIA TANAM JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Abd. Rahman Razak; Susanti Susanti; Nurhaeni Nurhaeni; Muh. Alwi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
Has done research on the study of the use of cocoa leaf litter for substitution sawdust and rice bran as a growing medium white oyster mushroom (Pleurotus ostreatus). This study aims to determine the ability of the cocoa leaf litter in substitute sawdust and rice bran as oyster mushroom media and to determine the nutrient value of the conversion of media into fruiting bodies of oyster mushrooms. Treatment comparison of leaf litter cocoa (SDK), sawdust (SG) and rice bran (DP) there are seven various ie first treatment / standard (SDK: 0 kg, SG: 5 kg, DP: 3 kg), second (SDK: 1 , 5 kg, SG: 5 kg, DP: 1.5 kg), third (SDK: 3 kg, SG: 5 kg, DP: 0 kg), fourth (SDK: 2.5 kg, SG: 2.5 kg DP: 3 kg), fifth (SDK: 5 kg, SG: 3 kg, DP: 0 kg), sixth (SDK: 5 kg, SG: 1.5 kg, DP: 1.5 kg), and seventh (SDK: 5 kg, SG: 0 kg, DP: 3 kg). The results showed that both treatments are best treated with a total weight of 181.122 g fruit.Keywords: cocoa leaf litter, white oyster mushroom